Туала удмурт проза: [антология] / [редактор-составитель С. В. Матвеев] - Матвеев Сергей Васильевич (Удмуртия, 2020)
Экземпляры: ф.1 (20200324) / Инвентарный номер: 60036 / Цена: / Сис.шифр: 84(2Рос=Удм)6-4 / Авт.знак: Т 81 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Удм)6-4^VLBC/PL